Alkaline Amendment for the Enhancement of Compost Degradation for Polylactic Acid Biopolymer Products. Issue 3 (2nd July 2016) - Hottle, Troy A.; Agüero, Marisol Luna; Bilec, Melissa M.; Landis, Amy E.
Abstract: This research evaluates the addition of alkaline amendments to enhance the degradation of polylactic acid polymers (PLA) in compost conditions. The use of compostable biopolymers is increasing in part because they are advertised as compostable. However, PLA degrades slowly compared to the organic wastes in compost and even when processed in commercial composting facilities may not fully break down. This results in the accumulation of biopolymers in compost facilities and increased difficulty in identifying and removing contamination from traditional plastics. Alkaline amendments were used to accelerate the degradation of two PLA products in compost conditions. Six flasks containing food scraps, compost inoculant, and an alkaline amendment were set up as bioreactors with half containing clear PLA and the others including opaque PLA. The six bioreactors were incubated for 22 days. The mass loss and final visual inspection, including microscopy, showed increased degradation within the bioreactors containing the alkaline treatments. These results show that the addition of alkaline amendment to composting systems may enable more effective processing of biopolymers, expanding the range and quantity of wastes that can be processes. The enhanced degradation of biopolymers in compost may enable greater diversion rates for institutions and cities by enabling the acceptance of biopolymers and any mixed organics stream which includes biopolymers wastes.